Improving the Quality of Learning New Testament Theology Courses with Quantum Learning Methods - Tari, Ezra; Pasande, Purnama; Tulaka, Elsye Evasolina; Rantesalu, Marsi Bombongan (International Journal for Educational and Vocational Studies, 2019)
The author does the learning process by using the quantum teaching method. This study departs from the writer's anxiety about the condition of student mastery of the material being studied. Inadequate campus facilities and lack of student interest in learning. As a result, students can not fulfill the assignments that have been given. Another issue that makes writers work hard is the average student from a remote area, where the learning process using information technology is still far from their reach. So the authors apply one of the learning processes using quantum teaching. The researcher examines the learning process using classroom action research. Based on the study conducted by the author in this paper, there are two important things that need to be learned, namely being able to do something, and be able to think for doing something. Teaching is a very important task in this world. Teachers should be able to influence human behavior from generation to generation. This is evident from the activities of the students in applying learning outcomes in class. Therefore, this paper contributes to a good learning process.